Needs Analysis for Flipped Classroom Integration Using Interactive H5P Modules in Herbal Pharmacology Learning - Kelik Widjonarko; Cecep Kustandi; Maria Paristiowati (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study conducted a needs analysis to inform the development of herbal pharmacology instruction using a flipped-classroom approach supported by interactive H5P (Hypertext Markup Language 5) modules at the Dharma Usada Study Program, Institut Nalanda. Employing a qualitative descriptive design, data were collected through structured classroom observations, semi-structured interviews with the course lecturer, and questionnaires administered to twenty-one students. Data were analyzed using descriptive qualitative methods and percentage calculations to identify instructional gaps and learner needs. Findings show learning remains lecture-dominant (78%) and reliant on presentation slides (91%), contributing to limited interaction and low student Engagement. Most students expressed readiness for technology-enhanced learning: 94% indicated strong interest in a flipped-classroom model supported by interactive H5P to promote autonomous learning and deeper conceptual understanding. Based on these results, the study recommends designing structured H5P modules featuring interactive videos, formative quizzes, and immediate feedback. This needs analysis provides an empirical basis for development, expert validation and pilot testing.